2014
DOI: 10.1016/j.bjane.2013.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of levobupivacaine and bupivacaine for supraclavicular block: a randomized double-blind comparative study

Abstract: 30 ml 0.5% bupivacaine and levobupivacaine provide similar block characteristics for supraclavicular block. Bupivacaine leads to faster motor and sensory block onset compared to levobupivacaine however similar duration of postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
3
6
0
1
Order By: Relevance
“…In the present study, onset of sensory block was 9.33+/-3.27 min in-group B whereas it was 16.13+/-2.83 min ingroup L. This difference was statistically significant (p<0.0001). These findings correlate with the findings of Cenk Ilham, et al [9] The sensory block onset time was 19.64+/-10.70 min in group B and 25.66+/-10.72 min in group L (p<0.036). However Jose Ricardo, et al found that there was earlier sensory block onset with levobupivacaine 0.5% as compared with bupivacaine 0.5% (p<0.05).…”
Section: Section: Anaesthesiasupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, onset of sensory block was 9.33+/-3.27 min in-group B whereas it was 16.13+/-2.83 min ingroup L. This difference was statistically significant (p<0.0001). These findings correlate with the findings of Cenk Ilham, et al [9] The sensory block onset time was 19.64+/-10.70 min in group B and 25.66+/-10.72 min in group L (p<0.036). However Jose Ricardo, et al found that there was earlier sensory block onset with levobupivacaine 0.5% as compared with bupivacaine 0.5% (p<0.05).…”
Section: Section: Anaesthesiasupporting
confidence: 92%
“…Jyoti P Deshpande et al observed that the duration of motor block was more with levobupivacaine (1049.46+/-95.02 min) as compared to bupivacaine (902.37+/-181.46 min) (p = 0.001). [13] Our results matched with the results in the studies done by C.R.Cox et al, [16] Baskan et al, [15] H. Evren et al, [12] Cenk et al, [9] and Dr Charu J Pandya and colleagues, [14] They all found no statistically significant difference between the motor block duration of the two drugs. Moreover, our result showed that sensory block tended to last longer as compared to motor block.…”
Section: Section: Anaesthesiasupporting
confidence: 89%
See 3 more Smart Citations